KepuasanÂ PernikahanÂ Â DitinjauÂ dariÂ BerpacaranÂ dan TidakÂ Berpacaran - Ardhianita, Iis; Andayani, Budi (Jurnal Psikologi, 2005)
GettingÂ marriedÂ  isÂ perceivedÂ asÂ anÂ  important phaseÂ inÂ humanÂ lifeâ€cycle.Â JustÂ likeÂ  fashion, marriageÂ hasÂ alsoÂ itsÂ ownÂ trendÂ orÂ mode.Â In IndonesiaÂ  theÂ  legendÂ  of Â  Siti Â  Nurbaya illustratingÂ aÂ kindÂ ofÂ maritalÂ arrangementÂ in,Â at least,Â theÂ firstÂ halfÂ ofÂ theÂ pastÂ century.Â SuchÂ a trendÂ  inÂ marriageÂ isÂ anyÂ moreÂ popularÂ theseÂ days. YoungÂ peopleÂ todayÂ mostlyÂ preferÂ toÂ marryÂ their ownÂ choices,Â thoseÂ alreadyÂ bondÂ inÂ engagement orÂ girlÂ orÂ boyÂ  friendsÂ theyÂ alreadyÂ mate.Â Another kindÂ  ofÂ  trendÂ  hasÂ  appearedÂ  recently.Â  Some moslemsÂ preferÂ toÂ marryÂ withoutÂ theÂ phaseÂ of datingÂ orÂ engagement.Â SomeÂ evenÂ marryÂ ones chose,Â orÂ arrangedÂ byÂ theirÂ ustadzÂ (spiritual leader). TheÂ purposeÂ ofÂ thisÂ studyÂ isÂ toÂ findÂ out whetherÂ  aÂ  differenceÂ  inÂ  theÂ  premarital relationship(withÂ versusÂ withoutÂ engagement orÂ dating)Â affectÂ couplesâ€™Â maritalÂ satisfaction. TheÂ  resultÂ  showsÂ  thatÂ  thereÂ  isÂ  aÂ  very significantÂ differenceÂ inÂ maritalÂ satisfaction betweenÂ  datingÂ  andÂ  nonâ€datingÂ  couples. ExplanationÂ uponÂ theÂ phenomenonÂ discussed. Keywords:Â maritalÂ satisfaction,Â datingÂ and non datingÂ couples